2015
DOI: 10.3168/jds.2014-8130
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of anti-Müllerian hormone in dairy heifers is positively associated with productive herd life

Abstract: Reliable biomarkers predictive of productive herd life (time in herd after birth of first calf) have heretofore not been discovered in dairy cattle. However, circulating concentrations of anti-Müllerian hormone (AMH) are positively associated with number of follicles or antral follicle count (AFC), ovarian function, and fertility, and approximately 25% of cows have a relatively low AFC and low AMH concentrations. The present study tested the hypothesis that heifers with the lowest AMH concentrations have subop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
72
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 37 publications
12
72
3
5
Order By: Relevance
“…In this study, dairy cows with a low AFC had a lower conception rate to first AI, greater number of AI to conceive and higher calving interval compared with cows with an intermediate or high AFC . Like our finding for dairy cows with low AMH as a heifer (Jimenez-Krassel et al 2015), overall pregnancy rate was lower for the dairy cows with a low compared with a high AFC . Another study shows that dairy cows with high AMH had greater pregnancy rates and lower incidence of pregnancy loss between days 30 and 65 of gestation (Ribeiro et al 2014).…”
Section: Fertilitysupporting
confidence: 36%
See 3 more Smart Citations
“…In this study, dairy cows with a low AFC had a lower conception rate to first AI, greater number of AI to conceive and higher calving interval compared with cows with an intermediate or high AFC . Like our finding for dairy cows with low AMH as a heifer (Jimenez-Krassel et al 2015), overall pregnancy rate was lower for the dairy cows with a low compared with a high AFC . Another study shows that dairy cows with high AMH had greater pregnancy rates and lower incidence of pregnancy loss between days 30 and 65 of gestation (Ribeiro et al 2014).…”
Section: Fertilitysupporting
confidence: 36%
“…4). Also, removal rate for poor reproductive performance compared with all other reasons for culling was greater for Q1 compared with Q2, Q3 and Q4 cows combined during the first lactation (Jimenez-Krassel et al 2015). This study, albeit conducted on a limited number of animals, indicates that a single determination of AMH concentrations in young adult Holstein heifers is predictive of their future herd longevity.…”
Section: Longevitymentioning
confidence: 91%
See 2 more Smart Citations
“…The plasma levels of AMH have been associated with the number of AFs in both taurine and zebu cattle (Jimenez‐Krassel et al., ; Modina et al., ). In this study, although the mRNA levels of AMH were similar in granulosa and cumulus cells from low and high AF cows, we observed that granulosa cells of Nelore cows with high AF had increased mRNA expression of AMHR2a compared with low AF cows.…”
Section: Discussionmentioning
confidence: 99%